Success of medical management of tubal ectopic pregnancy with Methotrexate in a tertiary hospital in North India - Juneja, Sunil K.; Jain, Kanupriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Unruptured ectopic pregnancy can be managed with surgery as well as systemic methotrexate. We aimed to study efficacy of medical management and factors affecting success in strictly selected patients. Methods: It was a three-year prospective observational study. 171 patients with ectopic pregnancy were screened and those fulfilling the strict study criteria were given systemic methotrexate. The single dose regimen was followed. Patients were observed for side effects and signs of rupture. Serial measurement of HCG levels was done to determine success or failure. Various factors were studied which had potential bearing on results. Results: Thirty-one patients received methotrexate. We had an overall success rate of 93%. Two of the participants had surgery due to failure. No major side effects were observed. Conclusions: Carefully selected patients of unruptured ectopic pregnancy can be safely and successfully treated with systemic methotrexate.